UPAYA PENINGKATAN MOTIVASI DAN PRESTASI BELAJAR PPKn DI ERA PANDEMIK COVID-19 MELALUI METODE CERAMAH BERVARIASI BERBANTU MEDIA XRECORDER TERHADAP SISWA KELAS IXD - Aman Aman (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2022)
During the COVID-19 pandemic, the world of education was greatly affected, so students were forced to study at home. The purpose of this study was to foster student motivation and achievement in participating in the teaching and learning process. The problems faced are students experience a decrease in motivation and learning achievement, so it needs creative and fun learning strategies. The method used in this research is a variety of lectures assisted by Xrecorder media to increase students' motivation and learning achievement. The results of the study showed that there was a significant influence between the Varied Lecture Method Assisted by Xrecorder Media, namely increasing students' motivation and learning achievement in Pancasila and Citizenship Education subjects. This can be seen from the data in the first cycle, the results are 73.3%, the second cycle is 83.3% and the third cycle is 96.6%. students' academic scores showed a significant increase from cycle I to cycle II, up 10% from cycle II to cycle III, an increase of 13.3%.